There Was No Pavement Then: Memories of Growing up in Petty Harbour-Maddox Cove. Booklet about growing up in Petty Harbour-Maddox Cove, NL. - Barrett, Terra (2015)
There Was No Pavement Then: Memories of Growing up in Petty Harbour-Maddox Cove. Booklet about growing up, children's games, hard work, holidays, community events, beliefs, and places in Petty Harbour-Maddox Cove, NL. Interviews and photographs completed during June, July and August 2014. Interview excerpts compiled, transcribed, and edited. Booklet launched July 9th, 2015 in Petty Harbour-Maddox Cove, NL.